Speciation of iron in soils and the relation with its concentration in fruits - Yaman, M (Maik Nauka/Interperiodica, 2001)
An attempt was made to identify the iron species that is most responsible for plant-available Fe. Iron concentrations in fruit samples were determined by using flame atomic absorption spectrometry (FAAS). The soil samples related to these fruits were also analyzed for Fe by using various digestion and extraction reagents. The relation between the fruit-Fe and soil-extractable-Fe concentrations was examined to explain the Fe uptake of fruit from soil. The probable chemical forms of Fe in the soil were evaluated for the speciation of Fe.
Keywords: Atomic-Absorption Spectrometry; Activated-Carbon Enrichment; Trace-Element Speciation; Vegetables; Matrices; Lead; Preconcentration; Manganese; Vanadium; Cadmium